Corporate Governance and Credit Risks (Survey Study on conventional Banks Listed in The Syrian Commission of Financial Markets and Securities) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The purpose of this study is to measure the extent of banks' commitment to corporate governance. And study the impact of this commitment on credit risks. The data collection of financial reports for conventional Banks Listed in The Syrian Commission of Financial Markets and Securities, and corporate governance reports during the period from 2016 to 2021. Panel data approach was employed in order to analyze data.                                                                                                         The results showed that the study sample banks achieved a good level of commitment to corporate governance. And the banks' commitment to corporate governance had a statistically significant inverse effect on credit risks, which it measured by Loan Loss Provision. That refers to the banks' commitment to corporate governance increases the attention of banks to configure the Loan Loss Provision to hedge to credit risks.